Learning SHAZAM : a computer handbook for econometrics - Duangkamon, Chotikapanich. (John Wiley & Sons, 1993)
Getting started with SHAZAM. Some basic ideas: statistical concepts for economists. Using SHAZAM for sampling experiments. Statistical inference I, II...